XVI Congress of the International Organization for Septuagint and Cognate Studies, Stellenbosch, 2016 - Kotzé, Gideon R.; Kraus, Wolfgang, 1955-; Meer, Michaël N. van der (Septuagint and cognate studies series, 2019)
This latest volume from the International Organization for Septauagint and Cognate Studies (IOSCS) includes the papers given at the XVI Congress of the IOSCS, South Africa, in 2016. The articles contribute to the study of the Septuagint and cognate literature by identifying and discussing new topics and lines of inquiry and developing fresh insights and arguments in existing areas of research. With contributions by seasoned specialists as well as up-and-comers from four continents (Africa, Asia, Europe, and North America), the volume is truly representative of the internation community of Septuagint scholarship. Scholars and students interested in different methods of studying the Septuagint corpora, the theology and reception of these texts, as well as the works of Josephus will find in this collection critical information for future work in Septuagint studies.